2008
DOI: 10.2174/092986708783503258
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Overcome or Circumvent P-Glycoprotein Mediated Multidrug Resistance

Abstract: Cancer patients who receive chemotherapy often experience intrinsic or acquired resistance to a broad spectrum of chemotherapeutic agents. The phenomenon, termed multidrug resistance (MDR), is often associated with the over-expression of P-glycoprotein, a transmembrane protein pump, which can enhance efflux of a various chemicals structurally unrelated at the expense of ATP depletion, resulting in decrease of the intracellular cytotoxic drug accumulation. The MDR has been a big threaten to the human health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 66 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…36 Various mechanisms have been identified that are involved in the different types and/or stages of cancers. 37,38 One primary mechanism involves the overexpression of P-glycoprotein (P-gp), which plays a vital role in the development of multiple drug resistance (MDR). 3943 P-gp, a member of ATP-binding cassette transporter, is one of the major drug efflux transporters and increased expression of P-gp leads to decreased drug accumulation in multidrug-resistant cells and the development of resistance to anticancer drugs.…”
Section: Resultsmentioning
confidence: 99%
“…36 Various mechanisms have been identified that are involved in the different types and/or stages of cancers. 37,38 One primary mechanism involves the overexpression of P-glycoprotein (P-gp), which plays a vital role in the development of multiple drug resistance (MDR). 3943 P-gp, a member of ATP-binding cassette transporter, is one of the major drug efflux transporters and increased expression of P-gp leads to decreased drug accumulation in multidrug-resistant cells and the development of resistance to anticancer drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Various mechanisms have been identified that are involved in the different types and/or stages of cancers [35,36]. One major mechanism involves the overexpression of P-glycoprotein (P-gp), which plays an important role in developing multiple drug resistance (MDR) [37].…”
Section: Resultsmentioning
confidence: 99%
“…Their lack of specificity requires a large dose to achieve clinical inhibition and thus results in toxicity. Numerous modifications of these inhibitors have appeared as promising candidates, but clinical trials continue to fail [113]. However, the use of these molecules in relation to nanomedicines is still an attractive strategy due to increased targeting and accumulation.…”
Section: Specific Resistance Mechanisms Overcome By Nanomedicinementioning
confidence: 99%